High rates of vaccine hesitancy among pregnant women during the coronavirus disease 2019 (COVID-19) pandemic in Japan - Aya Saitoh; Mayumi Takaku; Akihiko Saitoh (Taylor & Francis Group, 2022)
This study aimed to 1) determine the prevalence and contents of vaccine hesitancy among pregnant women during the coronavirus disease 2019 (COVID-19) pandemic and 2) evaluate its association with maternal sociodemographic factors. A cross-sectional survey was conducted between August and December 2020 among pregnant women between 28 and 32 weeks of gestation who received antenatal care at four clinics and hospitals in Niigata City, Japan. Vaccine hesitancy was assessed using the Parent Attitudes about Childhood Vaccines survey, and associations between vaccine hesitancy and sociodemographic factors were analyzed. In total, 113/200 (56.5%) subjects responded to the survey. Overall, 46/113 (40.7%) pregnant women were resistant or hesitant to receive the vaccine. Women with vaccine hesitancy were more likely to fear adverse reactions (concern 79.6%, not concerned 15.9%, and not sure 4.4%), safety (concerned 69.0%, not concerned 23.9%, and not sure 7.1%), and efficacy (concerned 47.8%, not concerned 35.4%, and not sure 16.8%) compared to those without vaccine hesitancy (P < .01, < .01, and <.01, respectively). In the multivariate logistic regression analyses, primipara women had higher rates of vaccine hesitancy than multipara pregnant women (odds ratio: 2.38, P = .04). In conclusion, the prevalence of vaccine hesitancy among pregnant Japanese women, especially primipara women, was higher than that in other countries during the COVID-19 pandemic. Their major concerns were adverse reactions, safety, and the efficacy of childhood vaccines. Further strategies are needed to provide appropriate vaccine information to prevent vaccine-preventable diseases in both infants and children.